TEHNICI SI METODE DE AMPRENTARE IN REABILITAREA IMPLANTO-PROTETICA - Bogdan Cutitaru; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
This study aims at individualizing an essential stage of treatment, namely the functional impression, the quantification of the decisive factors in the selection of the impression method, in full agreement with the particularity of the prosthetic field, in order to ensure an optimum management of the removable prosthetic therapy. Various types of impressions on implants have been recorded in the case of implanto-prosthetic rehabilitation, using different types of impression materials and different types of impression trays. Within implant impression, the impression material is applied by means of a syringe around the transfer devices and then the material loaded tray is applied in the oral cavity. Upon removal of the impression, the transfer devices remain fixed in the impression and then the impression is assessed from the point of view of the faithful representation of all the particularities of the prosthetic field. At the same time, the correct fixation of the devices is verified and whether there is or nor impression materials on their surface of adaptation with the implant.The choice of the impression material, corroborated with the impression method, is dictated by the particularities of the clinical case. The prosthetic solution of choice, as well as its performance requirements, are an essential condition in the choice of the impression material.